METHODS USED IN TEACHING HISTORY (Scientific journal of the Fergana State University, 2025)
When determining the methods of teaching history, it is necessary to initially consider the interdependence of education and upbringing, the continuous growth of students' ideological and political knowledge, the formation of skills in this regard, and their preparation for creative activity. For the successful implementation of educational goals, they should be determined on a scientific basis.